The Effect of Punishment, Training and Perceived Organizational Support Systems on the Work Discipline of PT Pelindo Multi Terminal Employees - Mita Rahmah; Kartini Harahap (Formosa Journal of Applied Sciences, 2023)
This study aims to analyze the effect of the punishment system, training, and perceived organizational support on the employee discipline. The form of research used is quantitative with an associative approach. Research sampling using the Slovin formula with a total of 63 respondents as samples. The primary data used in this study were obtained by distributing questionnaires directly and secondary data were obtained through literature studies. Data analysis methods in research use instrument tests, classical assumption tests, multiple linear analysis tests and hypothesis tests using SPSS. The results of the study showed that the variables of punishment system and perceived organizational support had a significant partial effect on the work discipline of PT Pelindo Multi Terminal employees. And the training variable has no significant effect on work discipline.